الظَّوَاهِرُ الصَّوْتِيَّةُ وَآَثَارُهَا فِي اخْتِلاَفِ الْقِرَاءَاتِ الْقُرْآنِيَّةِ - بثينة حساينية (My University, 2026)
Abstract: This thesis addresses the topic phonetic phenomena and their impact on the variations in Quranic readings through a theoretical and applied study. It aims to highlight the close relationship between the phonetic structure of the Quranic text and the diversity of its readings. The study focuses on revealing the role of phonetic phenomena such as assimilation, dissimilation, inversion, concealment, lengthening, and shortening in creating these vorcations, and demonstrating their impact on guiding and enriching the meaning while preserving the integrity of the Quranic text and not altering its original from. -------------------------- ملخص تناولت هذه االمذكرة موضوع الظواهر الصوتية وأثارها في اختلاف القراءات القرآنية من خلال دراسة نظرية وتطبيقية، حيث تهدف إلى إبراز العلاقة الوثيقة بين البنية الصوتية لنص القرآني وتنوع قراءاته. وانصبت هذه الدراسة على الكشف عن دور الظواهر الصوتية مثل الإدغام، والإظهار، والإقلاب، والإخفاء، والمد والقصر، في إحداث هذا الإختلاف، وإظهار مقدار أثرها في توجيه الدلالة وإغناءها، مع الحفاظ على سلامة النص القرآني وعدم المساس بأصله ----------------------------- Rèsumè: Cette thèse à traite du Sujet des Phenomènes Phonètiques et de leurs effets sur la variation des lectures coraniques à travers une ètude thèorique et appliquèe, car il vise à mettre en èvidence la relation ètroite entre la structure Phonètique du texte coranique et la diversitè de ses lectures. Cette ètude s’est attachèe à rèvèler le rôle des Phènomènes Phonètiques tels que l’assimilation, l’ambiguite, les inversions, la dissimilation, l’allongement et le raccourcissement dans la cause de cette diffèrence, et à montrer l’ètendue de leur impact pour orientre les sens et l’enrichir, tout en prèservant l’intègitè du texte coranique et sans compromettre son origine
Keywords: phonetic phenomena; Quranic readings; the phonetic structure of the Quranic text; integrity of the Quranic text; الظواهر الصوتية، القراءات القرآنية، البنية الصوتية للنص القرآني، سلامة النص القرآني.: phenomenes phonétiques; lecteures coraniques; la structure phonetiques du texte coranique; l’intégrite du texte coranique.